Breast Imaging After Dark. Issue 4 (28th April 2021) - Lane, Deanna L; Parikh, Jay R
Abstract: Patients may present to the emergency department with breast complaints due to traumatic or nontraumatic changes in the breast. Benign and malignant breast pathologies may mimic each other both in clinical presentation and imaging appearance. A complex cystic and solid mass seen on ultrasound in a patient with a palpable mass can represent breast cancer, abscess, or hematoma. A unilateral swollen breast may result from inflammatory breast cancer, mastitis, or other benign etiologies; correlation with clinical history, physical exam, and close follow-up are required to ensure complete resolution of symptoms. Uncommon breast entities such as granulomatous mastitis and breast implant–associated anaplastic large-cell lymphoma may cause changes in the appearance of the breast that prompt a patient to seek initial evaluation in the emergency department. Imaging evaluation of the breast in the emergency department is limited, and it is important that patients with a breast complaint be referred to a dedicated breast center for complete evaluation at an appropriate time interval after their discharge from the emergency department.